2003
DOI: 10.1109/ted.2003.810480
|View full text |Cite
|
Sign up to set email alerts
|

Noise modeling for RF CMOS circuit simulation

Abstract: The RF noise in 0.18-m CMOS technology has been measured and modeled. In contrast to some other groups, we find only a moderate enhancement of the drain current noise for shortchannel MOSFETs. The gate current noise on the other hand is more significantly enhanced, which is explained by the effects of the gate resistance. The experimental results are modeled with a nonquasi-static RF model, based on channel segmentation, which is capable of predicting both drain and gate current noise accurately. Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
218
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(226 citation statements)
references
References 43 publications
(86 reference statements)
7
218
1
Order By: Relevance
“…They believed that as Chen and Deens' model does not consider the carrier heating, the effect of mobility reduction gets largely compensated. They also believed that this is why Scholten et al (Scholten et al, 2003) were able to match the experimental result without considering carrier heating. Jeon et al also reported that the hot-carrier effect should be taken into account when modeling their 0.13 μm transistors (Jeon et al, 2007).…”
Section: Thermal Noise Modelingmentioning
confidence: 96%
See 1 more Smart Citation
“…They believed that as Chen and Deens' model does not consider the carrier heating, the effect of mobility reduction gets largely compensated. They also believed that this is why Scholten et al (Scholten et al, 2003) were able to match the experimental result without considering carrier heating. Jeon et al also reported that the hot-carrier effect should be taken into account when modeling their 0.13 μm transistors (Jeon et al, 2007).…”
Section: Thermal Noise Modelingmentioning
confidence: 96%
“…The induced gate noise can be naturally generated by using the segmentation method as presented in Scholten's paper (Scholten et al, 2003). However, the disadvantage of this approach is that it increases the number of transistors and therefore the simulation complexity, especially for the distortion analysis.…”
Section: Thermal Noise Implementationmentioning
confidence: 99%
“…(11), Γ is a constant, for most FETs, Γ ≈ 2/3 [27]. g fs is the FET forward transconductance and α is 1/f parameter used as a figure of merit for the FET 1/f noise.…”
Section: Noise Analysis Of the Designed Accelerometers And The Noise mentioning
confidence: 99%
“…It is prerequisite for the application of modern SOI technologies in RF circuits to better understand noise mechanisms [2][3][4][5]. For the applications in low noise CMOS RF circuits such as low noise amplifier (LNA), accurate modeling of noise is quite important.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, HF noise characterization and modeling for bulk and floating body SOI MOSFETs has been widely studied [6][7][8][9][10][11][12][13][14][15], and some modeling methods have been proposed. In [16], the authors proposed a channel segmentation model for accurate channel noise by several independent MOS model. In [17], the author presented a physical understanding of both intrinsic and extrinsic noise mechanisms in a MOSFET [18], a simple analytical model for the thermal channel noise of deep-submicron MOS transistors including hot carrier effects.…”
Section: Introductionmentioning
confidence: 99%